\(K_S^0-K_L^0\) Asymmetries in Weak Decays of Charmed Baryons - Fanrong Xu (Andromeda Publishing and Academic Services, 2021)
The \(K_S-K_L\) (SL) asymmetry occurs in the two-body charmed baryon decay with neutral kaon contained in their final states.In this work, based on the topological diagram approach and separated contributions calculated in naive factorization and the pole model, we provide explicit predictions on SL asymmetries for all the singly charmed baryon two-body decays. Especially, for the first time, we predict a sizable SL asymmetry for \(Ω_c\) decays in its unique decay channel \(Ω_c→ Ξ^0 K_{S,L}\). Among the four groups of decays in antitriplet charmed baryons, the \(R\) values for \(Ξ_c^+→ Σ^+ K_{S,L}\) and \(Ξ_c^0→ Σ^0 K_{S,L}\) are around \(-0.5\), which are promising to be measured. However, the other two groups \(Λ_c^+→ p K_{S,L}\) and \(Ξ_c^0→ Λ^0 K_{S,L}\) are relatively small. Our predictions are partially consistent with theoretical results provided by two other groups and an examination by future experiments is highly anticipated.